New Anti-CGRP Medications in the Treatment of Vestibular Migraine - Hoskin, Justin L.; Fife, Terry D. (Frontiers in Neurology, 2022)
Background Vestibular migraine (VM) is a condition associated with migraine headache, vertigo, dizziness, and balance disturbances. Treatment options are limited. It is unknown if new calcitonin gene-related peptide (CGRP) migraine medications have efficacy in treating VM. Methods We retrospectively reviewed all patients with VM who were prescribed one of the new CGRP medications between January 2016 and July 2020. In total, 28 patients met the inclusion criteria. We specifically evaluated the “older” CGRP medications including erenumab, galcanezumab, fremanezumab, and ubrogepant. Medical records for subsequent visits were assessed to monitor improvement described by patients. Results Of the 28 patients identified, 3 were lost to follow up. For the remaining 25 patients, we divided the patients based on a scale of “significant improvement”, “moderate improvement”, “mild improvement”, or “no improvement”. In total 21 of 25 patients demonstrated some level of improvement in their VM symptoms with 15 having moderate to significant improvement. Conclusion Results demonstrated a trend towards improvement, suggesting that the CGRP medications appear to be a decent treatment option. A prospective study evaluating CGRP medications in patients with VM would provide further information about this treatment option.